2008
DOI: 10.1159/000117815
|View full text |Cite
|
Sign up to set email alerts
|

Novel <i>SLC12A3</i> Mutations in Chinese Patients with Gitelman’s Syndrome

Abstract: Background: Inactivating mutations of the SLC12A3 gene are the most common cause of Gitelman’s syndrome (GS), a disorder inherited as an autosomal recessive trait. In a minority of cases, GS-like phenotypes are caused by mutations in the CLCNKB gene. Methods: We searched for SLC12A3 and CLCNKB gene mutations in 13 Chinese patients (9 males and 4 females, age 35 ± 14 years) from 8 unrelated families with the clinical and biochemical features of GS. All coding regions, including intron-exon boundaries, were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 35 publications
3
48
1
Order By: Relevance
“…The novel variants are seven missense mutations (p.C146F, p.T304M, p.N359D, p.T465P, p.P556L, p.N611T, and p.Y857C), a deletion of a guanine (c.402delG) that caused a frameshift that resulted in a truncated polypeptide with 141 acid residues (p.Arg135AlafsX8), and a splice mutation (c.964C2TOC), which was confirmed to lead to a shorter transcript characterized as skipping exon 7 by cDNA sequencing (p.Ala285 ArgfsX48). Additionally, seven mutations (p.T60M, p.G439S, p.S555L, p.R655C, p.R928C, p.Thr114A-lafsX142, and p.Arg959SerfsX11) identified in this study had been reported previously (8,10,(14)(15)(16)(17)(18)(19)(20). To both patients suspected of PA and GS, patient 1 showed compound heterozygosity for mutations of p.T60M and p.T304M, patient 2 was also a compound heterozygote with variants of p.T465P and p.N611T.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The novel variants are seven missense mutations (p.C146F, p.T304M, p.N359D, p.T465P, p.P556L, p.N611T, and p.Y857C), a deletion of a guanine (c.402delG) that caused a frameshift that resulted in a truncated polypeptide with 141 acid residues (p.Arg135AlafsX8), and a splice mutation (c.964C2TOC), which was confirmed to lead to a shorter transcript characterized as skipping exon 7 by cDNA sequencing (p.Ala285 ArgfsX48). Additionally, seven mutations (p.T60M, p.G439S, p.S555L, p.R655C, p.R928C, p.Thr114A-lafsX142, and p.Arg959SerfsX11) identified in this study had been reported previously (8,10,(14)(15)(16)(17)(18)(19)(20). To both patients suspected of PA and GS, patient 1 showed compound heterozygosity for mutations of p.T60M and p.T304M, patient 2 was also a compound heterozygote with variants of p.T465P and p.N611T.…”
Section: Resultssupporting
confidence: 76%
“…SLC12A3 and CLCNKB genes were analyzed as described (8,9). To analyze transcriptional profiles for the SLC12A3-splicing mutations, we extracted total RNA from blood using TRIzol (Invitrogen/Gibco).…”
Section: Mutation Analysismentioning
confidence: 99%
“…that ablates the key SPAK-OSR1 phosphorylation site in NCC is frequently detected in Asian patients with Gitelman's syndrome (Lin et al, 2005;Maki et al, 2004;Shao et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Thr60Ala mutation also markedly suppressed phosphorylation of Thr46 and Thr55, which indicates that phosphorylation of Thr60 is essential for enabling and/or maintaining the phosphorylation of other residues (Richardson et al, 2008). The importance of Thr60 in mediating NCC activation is further highlighted by the discovery of a Thr60Met NCC mutation in Asian patients with Gitelman's syndrome (Lin et al, 2005;Maki et al, 2004;Shao et al, 2008). The Thr60Met mutation in NCC might be more prevalent in Asian populations, because it has so far not been reported in other ethnic groups with Gitelman's syndrome (Ji et al, 2008).…”
Section: T Yeh Ya N Stqp Ge Prkvrp Tl a DL Hsf Lk Qe A Yeh Ya N Salp mentioning
confidence: 98%